The Effect Of SPIP Maturity, APIP Capability, and Risk Management On Corruption Prevention In Local Governments Of Bengkulu Province During 2021–2024 - Putri Deviana Naibaho; Robinson; E. Novita Sari (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Corruption remains a major challenge in local government administration because it can reduce the quality of governance, public trust, and regional development. Therefore, corruption prevention efforts are essential to support good governance. This study aims to examine the effect of Government Internal Control System (SPIP) maturity, Government Internal Supervisory Apparatus (APIP) capability, and risk management implementation on corruption prevention in district and city governments in Bengkulu Province. This research uses a quantitative approach with secondary data obtained from the Performance Reports of the Financial and Development Supervisory Agency (BPKP) for the period 2021–2024. The sample consists of 10 district/city governments, resulting in 40 observations. Data were analyzed using multiple linear regression. The results show that SPIP maturity has a positive and significant effect on corruption prevention. Meanwhile, APIP capability and risk management do not have a significant effect on corruption prevention. These findings indicate that strengthening internal control systems plays a more important role in supporting corruption prevention efforts than improving supervisory capability and implementing risk management that is still focused on administrative compliance. The results support the Fraud Triangle Theory, particularly in explaining the importance of reducing opportunities for corruption through effective internal control systems.